2015
DOI: 10.1177/0014402914563701
|View full text |Cite
|
Sign up to set email alerts
|

Constructing and Validating a Multiple-Indicator Construct of Economic Hardship in a National Sample of Adolescents with Disabilities

Abstract: The purpose of the current study was to develop a multi-indicator construct of economic hardship among adolescents with disabilities ( N = 9,230) participating in the National Longitudinal Transition Study–2, the largest, most comprehensive investigation of adolescents with disabilities ever conducted. Five theoretically relevant indicators (i.e., family income, head-of-household education, head-of-household employment, participation in social programs, and lack of resources) contributed to the formation of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 38 publications
1
32
1
Order By: Relevance
“…Numerous researchers have reported that females, students of color (i.e., particularly African American and Native Americans), and youth with disabilities from low-SES backgrounds have poorer posthigh-school employment rates than do males, Caucasians, and those from middle and high SES backgrounds (Blackorby & Wagner, 1996; Doren & Benz, 1998; Sima et al, 2015). These findings are consistent with those from community samples and likely reflect a constellation of challenges facing these populations including those encompassed in family SES (Murray et al, 2015; Swartz et al, 2017).…”
Section: Transition To Adulthood and Disabilitysupporting
confidence: 84%
See 1 more Smart Citation
“…Numerous researchers have reported that females, students of color (i.e., particularly African American and Native Americans), and youth with disabilities from low-SES backgrounds have poorer posthigh-school employment rates than do males, Caucasians, and those from middle and high SES backgrounds (Blackorby & Wagner, 1996; Doren & Benz, 1998; Sima et al, 2015). These findings are consistent with those from community samples and likely reflect a constellation of challenges facing these populations including those encompassed in family SES (Murray et al, 2015; Swartz et al, 2017).…”
Section: Transition To Adulthood and Disabilitysupporting
confidence: 84%
“…Despite low rates of employment and postsecondary participation among young adults with disabilities, little attention has been devoted to understanding potential interrelationships between these activities. Among normative samples, participation in some form of postsecondary education contributes to greater employment stability and higher quality employment (Neumark & Rothstein, 2006; Vuolo et al, 2016), issues that remains critically important to adults with disabilities who are disproportionately represented in poverty (Murray et al, 2015). Evidence derived from normative samples also indicates that participation in these activities is often interrelated such that some youth who attend postsecondary school delay engaging in employment until finishing school (Eliason et al, 2015; Vuolo et al, 2014) whereas others pursue more intensive employment directly following high school, but then may enter postsecondary school after working for several years in an effort to achieve higher quality work opportunities (Vuolo et al, 2014).…”
Section: Transition To Adulthood and Disabilitymentioning
confidence: 99%
“…This sense of security is derived from access to a supportive and responsive adult, which provides the confidence, or self‐assuredness, to take on new challenges but may also assist in recovering from setbacks that occur (Armsden & Greenberg, 1987; Bowlby, 1973; Pianta, 1999). The felt security derived from having access to a supportive adult relationship may be particularly important for youth experiencing disability or other academic risks because these students are more likely to also experience concurrent difficulties in other areas of functioning (e.g., social, emotional, behavioral), in other social relationships (e.g., parents & peers), and in communities outside of school (Al‐Yagon, 2012; Ansari et al, 2020; Murray et al, 2015; Panicker & Chelliah, 2016). For these youth, supportive teacher–student relationships may help to buffer the negative effects of such risks on educational outcomes (Murray, 2009; Sharkey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Results from the first causal comparative study identified predictors of school dropout for students with LD such as (a) grades and engagement in high-risk behaviors, (b) family and parent expectations, and (c) school environment (Doren, Murray, & Gau, 2014). Findings from the second causal comparative study identified five significant indicators of economic hardship including (a) family income, (b) head-of-household education, (c) head-of-household employment, (d) participation in social programs, and (e) lack of resources (Murray, Doren, Gau, Zvoch, & Seeley, 2015).…”
Section: Resultsmentioning
confidence: 99%